Melt Electrowriting of a Photo‐Crosslinkable Poly(ε‐caprolactone)‐Based Material into Tubular Constructs with Predefined Architecture and Tunable Mechanical Properties. Issue 7 (14th July 2022) - Pien, Nele; Bartolf‐Kopp, Michael; Parmentier, Laurens; Delaey, Jasper; De Vos, Lobke; Mantovani, Diego; Van Vlierberghe, Sandra; Dubruel, Peter; Jungst, Tomasz
Abstract : Front Cover : Melt electrowriting (MEW) is a novel additive manufacturing technique currently limited by the material selection. The cover image, by Tomasz Jungst and co‐workers in article number 2200097, depicts a construct made during the approach to establish new materials for MEW based on an acrylate‐endcapped urethane‐based polymer (AUP). Blending AUP with the gold‐standard material in MEW, poly‐( ε ‐caprolacton), enables tailoring mechanical properties of constructs via photo‐crosslinking.